The correlation of neuropsychological evaluation with 11C-PiB and 18F-FC119S amyloid PET in mild cognitive impairment and Alzheimer disease. Issue 16 (April 2020) - Park, Su Yeon; Byun, Byung Hyun; Kim, Byung Il; Lim, Sang Moo; Ko, In Ok; Lee, Kyo Chul; Kim, Kyeong Min; Kim, Yu Kyeong; Lee, Jun-Young; Bu, Seon Hee; Kim, Jung Hwa; Chi, Dae Yoon; et al.
Abstract : Abstract: For the diagnosis of mild cognitive impairment (MCI) and Alzheimer disease (AD), variable neuroimaging and neuropsychological tests have been used. We aimed to evaluate the correlation of neuropsychological domain with new amyloid positron emission tomography (PET) study and to validate the availability of new PET tracer. We enrolled 20 patients who underwent 11 C-PiB-PET/CT, new PET tracer 18 F-FC119S PET/CT from November, 2014 to July, 2015. Among them, 10 patients were diagnosed with AD and 10 patients with MCI. The current version of Seoul Neuropsychological Screening Battery (SNSB) II was performed for cognitive evaluation. Each parameter of SNSB was compared between 2 patient groups. Spearman correlation analysis between value of SNSB domain and standardized uptake value ratio (SUVR) of PET was also performed. The AD group presented significant poor z-score in Korean-Boston Naming Test(K-BNT) ( P = .01), copy score of Rey Complex Figure Test (RCFT) ( P = .049), immediate ( P = .028)and delayed memory of Seoul Verbal Learning Test (SVLT) ( P = .028), recognition of RCFT ( P = .004), "animal" of Controlled Oral Word Association Test (COWAT) ( P = .041), color reading of Korean-Color Word Stroop test (K-CWST) ( P = .014), and Digit Symbol Coding (DSC) ( P = .007) compared with MCI group. That means, except attention domain, all other cognitive domains were relatively impaired in AD compared with MCI. In correlation analysis, we found that poor performances on copy score of RCFT in MCI groups were associated with great beta amyloid burden in frontal area in both 11 C-PiB-PET/CT and 18 F-FC119S PET/CT. In AD group, 18 F-FC119S PET presented more extensive correlation in each cognitive domain with multiple cortical areas compared with 11 C-PiB-PET. The degree of amyloid burden assessed on 18 F-FC119S PET was significantly correlated with neuropsychological test in AD, and also MCI patients. The combination of neuropsychological evaluation with novel 18 F-FC119S PET/CT can be used for valid biomarker for MCI and AD.